The nature of Islamic banking and solvency stress testing - Jobst, Andreas A.,Solé López-Pinto, Juan (International Monetary Fund, 2020)
This paper provides a conceptual overview of key aspects of the design and implementation of solvency stress testing of Islamic banks. Based on existing regulatory standards and prudential practice, the paper explains how Islamic finance principles and their impact on various risk drivers affect the capital assessment of asset-oriented financial intermediation under stress. The formal specification of these risk factors helps operationalize and integrate the stress testing of Islamic banks within established frameworks for financial stability analysis
10.5089/9781513550886.001
Keywords: Graue Literatur; Banks and Banking; Finance: General; Islamic Banking and Finance; Central Banks and Their Policies; General Financial Markets: Government Policy and Regulation; Comparative Analysis of Economic Systems; Other Economic Systems: Public Economics; Financial Economics; Financing Policy; Financial Risk and Risk Management; Capital and Ownership Structure; Value of Firms; Goodwill; Banks; Depository Institutions; Micro Finance Institutions; Mortgages; Financial Institutions and Services: Government Policy and Regulation; Financial services law & regulation; Finance; Islamic banking; Market risk; Banking; Credit risk; Stress testing; Financial services; Financial regulation and supervision; Financial sector policy and analysis; Islamic finance; Financial risk management; Banks and banking; Islamic countries; Banks and banking; stress testing; Islamic finance principles; capital adequacy; shari’ah compliance